High-spin states analysis in 103Mo nucleus with theInteracting Boson- Fermion Model (IBFM) - Nabeil Ibraheem Fawaz (مجلة جامعة الانبار للعلوم الصرفة, 2012)
Abstract: The Interacting Boson-Fermion model (IBFM) has been applied on the neutron-rich 103Mo nucleus for the first time. The IBFM succeeded in describing this nucleus for both energy excitations, electromagnetic and moment properties. The IBFM produces better agreement with experimental results than other theoretical models such as cranked shell model (CSM) and rigid triaxial rotor-plus-particle (RTRP) model. Some new data have been presented for the first time.